2015
DOI: 10.1111/iej.12476
|View full text |Cite
|
Sign up to set email alerts
|

Novel keratin preparation supports growth and differentiation of odontoblast‐like cells

Abstract: The presence of keratin enhanced odontoblast cell behaviour. Keratin hydrogels may be a potential scaffold for pulp-dentine regen-eration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…Current in vitro evidence suggests other potential drug delivery systems for bioactive molecules, such as biodegradable polymer matrix of lactide and glycolide (Mathieu et al 2013), porous silk fibroin scaffolds (Yang et al 2015), poly-2-hydroxyethyl methacrylate (polyHEMA)-based hydrogel (Takeda et al 2015), tricalcium phosphate microsphere-hydrogel composite (Lee et al 2014). In addition, biomaterials that can be used as scaffolds for VPT have recently been suggested and could enhance proliferation and differentiation of human dental pulp cells, such as polycaprolactone/submicron bioactive glass hybrid composites (Wang et al 2016a), a chitosan-based scaffold (Bellamy et al 2016) and keratin hydrogel (Sharma et al 2016).…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…Current in vitro evidence suggests other potential drug delivery systems for bioactive molecules, such as biodegradable polymer matrix of lactide and glycolide (Mathieu et al 2013), porous silk fibroin scaffolds (Yang et al 2015), poly-2-hydroxyethyl methacrylate (polyHEMA)-based hydrogel (Takeda et al 2015), tricalcium phosphate microsphere-hydrogel composite (Lee et al 2014). In addition, biomaterials that can be used as scaffolds for VPT have recently been suggested and could enhance proliferation and differentiation of human dental pulp cells, such as polycaprolactone/submicron bioactive glass hybrid composites (Wang et al 2016a), a chitosan-based scaffold (Bellamy et al 2016) and keratin hydrogel (Sharma et al 2016).…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…This fibrous protein is present not only in the native ECM but also in different districts including wool, hair, fur, hooves, and feather. 20,21 Recent works demonstrated that keratin-based materials may be easily designed in the form of films, 22 hydrogels, 23,24 sponges, 25 fibers, 26 without altering the natural pathway of amino acid sequences, similarly to those required to promote cell adhesion in ECM. 21,27 In particular, wool keratin is biocompatible, biodegradable, nonimmunogenic, does not induce inflammatory response and promotes wound healing by stimulating human keratinocytes migration.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, woolderived keratin presents both RGD and LDV cell adhesion sequences. 43,44 These sequences bind ανβ3 and α4β1 integrins overexpressed on the endothelium of the tumor neovasculature and on many types of cancer cells. [45][46][47] To investigate the ability of our innovative delivery system to vehiculate PTX to cells grown in 2D model, we took advantage of PTX labeled with a thiophene-based fluorescent dye (PTX-F35), a previously reported fluorescent PTX derivative, 48 to perform cytofluorimetric uptake assays over time.…”
Section: Discussionmentioning
confidence: 99%